1993
DOI: 10.1212/wnl.43.4.775
|View full text |Cite
|
Sign up to set email alerts
|

Brain magnetic resonance imaging in coronary artery bypass grafts

Abstract: We undertook a study to determine (1) the frequency and prognostic significance of preexisting MRI brain abnormalities in patients undergoing coronary artery bypass grafts (CABG) and (2) whether MRI can detect surgery-related brain damage in 31 neurologically asymptomatic CABG patients (mean age, 61.0 +/- 6.6 years). MRIs were performed within 7 days before and 8 to 17 days after surgery. When we compared the preoperative images with those of 31 age- and risk factor-matched neurologically asymptomatic controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 0 publications
2
15
0
2
Order By: Relevance
“…We detected lacunar infarcts on MR images in 86 (57.0%) of our 151 subjects. Our finding of frequent association of lacunar infarcts in CABG candidates is comparable with those reported in studies of Goto et al [25](54%) and Schmidt et al [30](58%). We previously found that carotid stenosis and ischemic heart disease were predictors of silent cerebral infarcts in the basal ganglia, and suggested that these were manifestations of the progression of generalized atherosclerosis [31].…”
Section: Discussionsupporting
confidence: 92%
“…We detected lacunar infarcts on MR images in 86 (57.0%) of our 151 subjects. Our finding of frequent association of lacunar infarcts in CABG candidates is comparable with those reported in studies of Goto et al [25](54%) and Schmidt et al [30](58%). We previously found that carotid stenosis and ischemic heart disease were predictors of silent cerebral infarcts in the basal ganglia, and suggested that these were manifestations of the progression of generalized atherosclerosis [31].…”
Section: Discussionsupporting
confidence: 92%
“…neuropsychological deficits in a small patient group, Schmidt et al 49 failed to demonstrate CABG-related microembolic lesions on postoperative MRIs. We also did not find a correlation between neuropsychological deficits and the HITS-induced changes of rCMRGlc deltamax , which might have two reasons.…”
Section: Discussionmentioning
confidence: 96%
“…35 Only 2 previous studies have examined control subjects who did not undergo CABG. 15,33 Other limitations of previous reports include the use of low-field-strength scanners (0.15 DWI of a 64-year-old woman (patient 2, Table 1) without any demonstrable neurological deficits after CABG. Preoperative scan, performed 2 days after a diagnostic cardiac catheterization, revealed a small diffusion abnormality on the right corona radiata.…”
Section: Discussionmentioning
confidence: 99%